The Influence of Leadership Style and Work Environment on the Performance of Public Elementary School Teachers in Ulubongka District, Tojo Una-Una Regency - Fadilah; Andi Indriani Ibrahim; Lindanur Sipatu; Wisra Matalatta; Rosida P. Adam (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of leadership style and work environment on the performance of public elementary school teachers in Ulubongka District, Tojo Una-Una Regency. Using a quantitative causal design, data were collected through questionnaires from all 30 teachers and analyzed using multiple linear regression. The results show that leadership style and work environment each have a positive and significant effect on teacher performance, both partially and simultaneously. The model explains 92,1% of the variance in teacher performance. These findings highlight the importance of effective school leadership and a conducive work environment in improving teacher performance. Keywords: Leadership, Work Environment, Teacher Performance